2015
DOI: 10.5424/sjar/2015131-6050
|View full text |Cite
|
Sign up to set email alerts
|

Online laboratory evaluation of seeding-machine application by an acoustic technique

Abstract: RESEARCH ARTICLE OPEN ACCESSsliding or bouncing seeds on the sticky belt, especially at high belt speed (Kocher et al., 1998). However, it is convenient and has been tried by some researchers for evaluating a single row seed metering mechanism (Panning, 1997;Molin et al., 1998;Singh et al., 2005;Anantachar et al., 2010;Zhan et al., 2010;Li et al., 2012;Önal et al., 2012;Yasir et al., 2012). Among other alternative techniques, an opto-electronic seed spacing determination system has been developed (Kocher et al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…The keywords that emerged during the rapid development stage are "performance", "optimization", "spacing uniformity", "uniformity", and "simulation". These representative keywords indicate that the content of scientific research in recent years has focused on the simulation, consistency, operability and practical performance of machines [8,9].…”
Section: Keyword Co-occurrence Analysismentioning
confidence: 99%
“…The keywords that emerged during the rapid development stage are "performance", "optimization", "spacing uniformity", "uniformity", and "simulation". These representative keywords indicate that the content of scientific research in recent years has focused on the simulation, consistency, operability and practical performance of machines [8,9].…”
Section: Keyword Co-occurrence Analysismentioning
confidence: 99%
“…The change in the equivalent dielectric constant as the seeds pass through the detection area of the capacitance sensor causes a change in the capacitance output value Complex ambient light and dust have less effect on capacitive sensors The method could detect more than one seed at a time Capacitance sensors are easily influenced by the seed water content, machine vibrations, temperature, and parasitic capacitance Seeds with smaller volumes do not generate detectable variation in the dielectric coefficient [13][14][15][16][17] Machine vision…”
Section: Principlesmentioning
confidence: 99%
“…Several studies have reported that machine vision and image processing methods achieved different degrees of success [13,14]. However, these methods suffer many disadvantages, such as the need for complex calibration and data processing operations, expensive cameras and software, high labor requirements, artificially lit environments, and long process times [15][16][17]. The machine vision method can effectively monitor two or more simultaneously falling seeds, but the method is extremely demanding in terms of the monitoring environment, thus limiting its application in agricultural production [11].…”
Section: Plos Onementioning
confidence: 99%
“…There have been scientific, patent and specialist publications giving examples of solutions based on optical sensors [8]. The detectability of various sensors was tested in earlier studies [9][10][11]. A linear image intensifier could be used as an alternative, but this solution is still expensive and requires complex software for image analysis [12].…”
Section: Introductionmentioning
confidence: 99%